Hubungan Pembelajaran Daring Di Masa Pandemi Covid-19 Dengan Stress Akademik Mahasiswa S1 Keperawatan - Rohmat Bali Edy; Feriana Ira Handian; Nining Loura Sari (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2022)
Online learning is learning that uses the internet network with accessibility, connectivity, flexibility and the ability to bring up various types of learning interactions. Ineffective online learning due to limited facilities, supporting facilities and infrastructure in online learning such as cellphones, laptops, internet networks and also quotas for accessing the internet can cause psychological disorders, namely stress. Stress experienced by students that occurs at school/college is called academic stress. The design of this study used a correlative design with a cross sectional approach. The research population was 111 undergraduate nursing students at Stikes Maharani Malang and the research sample was 88 respondents with calculations using the Slovin formula with determination using Stratified Random Sampling. The data collection technique used instruments in the form of an online learning questionnaire and an ESSA (Educational Stress Scale Adolescent) academic stress questionnaire. The data analysis method used is the Spearman Rank test. The results showed that most of the 51 (58.0%) respondents experienced poor online learning and most of the 58 (65.2%) respondents experienced very severe academic stress. The results of the Spearman Rank test show that there is a relationship between online learning during the Covid-19 pandemic and the academic stress of undergraduate Nursing students at STIKes Maharani Malang, the p value = (0.000) < (0.05), meaning that someone who experiences online learning is not good then can cause severe academic stress. The suggestion of this research is that further research is needed to determine other factors that cause academic stress such as family economic status and the ability to use electronic media.